Constitutional and Legislative Framework for Sustainable Environmental Management in Nigeria: Issues and Challenges - Ekpenisi, Collins; Okonji, Charles; Okpoko, Mercy; Hassan Ismaila Adebowale; Aidonojie, Endurance (CV. Pustaka Parawali, 2025)
The long-term survival and sustenance of every society are contingent on sustainable environmental management. For a country like Nigeria, with a continuous increase in the rate and intensity of environmental degradation, sustainability practices, laws, and institutions are even more critical. Rapid industrialisation, unchecked oil exploration, and ineffective regulatory enforcement have all contributed to this problem. This seemingly perpetual destruction of the environment ought to be addressed effectively, and specifically by using the country’s legal and institutional frameworks to effect some degree of positive change. However, lapses and gaps in the execution of crucial legislation, combined with gross political negligence and unwillingness to act, have hindered any form of progress. This paper examines Nigeria’s existing legal and institutional frameworks, highlights and evaluates challenges that delimit their effectiveness, and offers some insights into their apparent and expected contributions to environmental sustainability. The paper employs a doctrinal method and relies heavily on primary legislation, judicial authorities, and secondary academic sources, particularly studies from expert legal, socio-political, and environmental scholars. The study concludes with a considerable number of recommendations that suggest important areas of improvement in Nigeria’s broader plan for effective environmental management. This research contributes a comprehensive analysis of Nigeria’s constitutional and legislative frameworks for environmental management, identifying legal gaps and proposing actionable reforms to strengthen sustainable environmental governance.